Is Plaque Removal Efficacy of Toothbrush Related to Bristle Flaring? A 3-month Prospective Parallel Experimental Study - Tangade, PS; Shah, AF; Tl, R; Tirth, A; Pal, S (Ethiopian journal of health sciences, 2013)
Toothbrushes are over-the-counter products; therefore, no special instruction is given to users when they purchase. There are scarce published studies that have investigated about how often toothbrushes should be replaced. Thus, this study aimed to verify the impact of the Progressive Toothbrush Bristle Flaring on plaque control efficacy of toothbrush. Thirty six subjects were randomly selected and underwent complete oral prophylaxis 10 days prior to the Baseline plaque recording. All subjects were provided with new similar toothbrushes and were divided into two groups. New Brush Group changed toothbrush every month and Old month Group used single toothbrush for the whole period of the study. Both groups were assessed for plaque accumulation every month using Turesky et al, (1970) modification of the Quigley and Hein (1962) plaque index. Toothbrush head was photographed and assessed by measuring the brushing surface area on standardized photographs using National Institutes of Health Image Analysis Program (USA). Both groups showed similar plaque scores at the 40(th) day; progressive increase in the plaque scores in group without changing the toothbrush were recorded at the 70(th) and 100(th) days. As toothbrush flaring increased, the plaque scores also increased in the Old Brush Group. Highest plaque accumulation was recorded in Mandibular Lingual aspects in Old Brush Group. Progressive increase was seen in the plaque scores with increase in toothbrush bristle flaring.